FRI0003 ACPA response against fibrinogen epitopes citrullinated in vivo in the synovial membrane in RA patients detected with an autoantibody microarray. (23rd January 2014) - Ossipova, E.; Hansson, M.; Mathsson, L.; Klareskog, L.; Jakobsson, P.-J.; Rönnelid, J.
Abstract : Background: Citrullination is a post-translational modification of proteins catalyzed by specific peptidylarginine deiminases, which modify arginine residues to citrulline. Citrullinated proteins are frequently detected in various inflammatory states including rheumatoid arthritis, and a lot of attention has been drawn to the presence of auto-antibodies targeting proteins containing citrulline 1 . These antibodies are found in 60% cases of RA and are used as a diagnostic marker. Objectives: Using high resolution mass spectrometry (MS) we have first identified citrullinated peptides corresponding to amino acids 559-575 of fibrinogen α-chain and corresponding to amino acids 52-77 of the fibrinogen β-chain in synovial tissues from patient with RA 2 . In this work we have also identified citrullinated peptide corresponding to amino acids 580-599 of fibrinogen α-chain but decided do not include it to publication due to possible deamidation of asparagine or glutamine, which leads to the same mass shift as deamidation of arginine. In this follow-up study we test sera from RA patients for anti-citrullinated protein antibodies (ACPA) response against MS identified citrullinated fibrinogen peptides. Methods: In this work a microarray assay based on Phadia's ImmunoCAP ISAC® system, where reactivity to more than 100 antigens can be analyzed simultaneously using small volumes of sera, was employed. Four synthetized fibrinogen peptides (containing citrulline at the positions 573 (Fib 573), 591 (Fib 591) within the α-chain and at the positions 72 (Fib 72) and 74 (Fib 74) within the β-chain, respectively) were immobilized onto a chemically modified glass slide in an arrayed fashion. After binding of antigens to the glass surface diluted serum from 936 RA patients (404 CCP positive and 532 CCP negative) and 461 healthy controls from the Epidemiological Investigations in Rheumatoid Arthritis (EIRA) case control cohort were applied into reactions sites on the glass slides, followed by fluorescent-labeled anti-human IgG antibody and scanning in a laser scanner. Cutoff values were determined as the 98th percentile of the healthy control responses. Results: We found that 31% (among them 87% are CCP positive) of patients were positive to Fib573 peptide. For the Fib2591 peptide, the corresponding figures were 10% (65%), for the Fib74 peptide 28% (68%) and for the Fib72 peptide 20% (68%). Conclusions: Here we show extensive autoantibody reactivity against fibrinogen epitopes that are citrullinated in vivo in RA synovial membranes. A substantial part of the ACPA peptide reactivities were found among anti-CCP2 negative RA patients. The results suggest the use of these citrullinated fibrinogen peptides as biomarkers in RA. References: Schellekens, G. A. et al., The diagnostic properties of rheumatoid arthritis antibodies recognizing a cyclic citrullinated peptide. Arthritis Rheum 43(1), 155 (2000). Hermansson, M. et al., MS analysis of rheumatoid arthritic synovial tissue identifies specific citrullination sites on fibrinogen. Proteomics Clin Appl 4(5), 511. Disclosure of Interest: None Declared